Physical property of multi walled carbon nanotube reinforced aluminium nano composite - Maleque, Md. Abdul (2013)

(untitled)
The unique properties of carbon nanotube such as high strength, elastic modulus, flexibility and high aspect ratios changed the direction of the research in the field of fibrous materials and are attracting much interest as reinforcement to aluminium matrix for carbon nano tubes aluminium matrix (MWCNT-Al) nano-composite. However, the quality of the dispersion is the major concerning factor which determines the homogeneity of the enhanced physical, mechanical and tribological properties of the composite. This work study the physical property of the MWCNT-Al nano-composite prepared with different weight percentage of MWCNT in aluminium matrix using powder metallurgy route under high energy planetary ball milling operations at different time intervals. The bulk nano-composite powder was sintered using hot isostatic process at the temperature of 500oC for 60 minutes under argon gas. The experimental results showed significant amount of mass reduction up to 55% which ensure light weight material as a result of the effect of milling time and controlled atmospheres in the HIP machine. Addition of small percentage of MWCNT in aluminium matrix is the main contributing factor in achieving mass reduction, hence reduced the density of MWCNT-Al nano-composite material compared to pure aluminium.